Ezekiel and Eschatological Violence : Pentecostal Interpretation of Ezekiel 36-39 and Revelation 19-20 - Jackson, Alicia R. (Journal of Pentecostal Theology Supplement Series, 2025)
This monograph explores the topic of eschatological violence in Pentecostal biblical interpretation of Ezek. 36.16-39:29, Rev. 19.11-21, and Rev. 20.7-10. By reviewing Pentecostal reception history of these texts, considering the influence of classical dispensationalism on Pentecostal biblical interpretation and eschatology, this study offers a peace reading that aligns with both early Pentecostal writers and contemporary Pentecostal scholars whose eschatology departs from classical dispensationalism. This monograph builds a case for envisioning a hopeful and proleptic premillennial eschatology that emphasizes the peace and reconciliation of the gospel more than 'end times' war and violence.